Tumor-intrinsic interferon signaling drives pancreatic cancer resistance to tumor mucin1-targeted CAR T cell therapy - Zhou, Ru; Mayberry, Rebecca; Firmin, Taina; Sanders, Alexa; Brouwer, Cory; Maher, John; Mukherjee, Pinku (Frontiers in Immunology, 2025)
Pancreatic cancer (PC) remains one of the most challenging cancers and has the worst prognosis. Tumor-associated MUC1 (tMUC1) is overexpressed and aberrantly glycosylated in over 80% of human pancreatic ductal adenocarcinoma (PDA). Chimeric antigen receptor (CAR) engineered T cells are an emerging cancer immunotherapy strategy and recently, we successfully engineered tMUC1-specific human and mouse CAR T cells and demonstrated their effectiveness as monotherapy against PDA in vitro and in vivo. In this study, we observed varying sensitivity among human PDA cell lines in response to tMUC1-targeted CAR T cell cytolysis. Notably, highly resistant HPAFII cells released greater amounts of interferon (IFN)-regulated ICAM-1, CXCL10, and CXCL11 compared to the more sensitive MiaPaCa-2 cells following CAR T cell challenge. Blocking IFN signaling using Ruxolitinib, a JAK1/2 inhibitor (JAKi), significantly reduced the upregulation of ICAM-1 and CXCL10. Western blot analysis revealed that both type I and type II IFN signaling pathways were elevated in PDA cells upon CAR T cell treatment. JAKi effectively suppressed this signaling response, with a more pronounced impact on the type I IFN pathway. Importantly, both IFN blockade and transient knockdown of IFN receptors significantly enhanced the sensitivity of PDA cells to CAR T cell-mediated cytolysis in vitro. Further mechanistic study revealed that CAR T cells partially lose their cytolytic potential after engaging with PDA cells. Treatment with CAR T cells triggered the up-regulation of immune checkpoint PD-L1 expression on PDA cells via tumor cell’ own IFN signaling. Thus, blocking PD-L1 in HPAFII enhanced its response to CAR T cells. Similarly, neutralizing CXCL10 enhanced CAR T cell killing of HPAFII cells suggested CXCL10’s involvement in resistance to CAR T cell cytolysis. RNA-seq data indicated higher expression of multiple genes along the IFN signaling pathway which were associated with poor prognosis in PDA patients. Taken together, tumor intrinsic IFN signaling may drive immune evasion in PDA cells against tMUC1-targeted T cell-mediated immunotherapy. This identifies tumor IFN signaling as a potential therapeutic target to improve CAR T cell efficacy in PDA treatment.